2011
DOI: 10.4319/lo.2011.56.3.1008
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of salinity and disturbance regime on active and dormant crustacean communities

Abstract: In a large-scale and long-term outdoor mesocosm (400-liter) experiment, we studied the interacting effects of salinity and disturbance (hydrological) regime on the active and dormant crustacean communities of Mediterranean temporary wetlands (Camargue, southern France). Sixty-four mesocosms, inoculated with a regional species pool (mixed dormant egg banks), were exposed to a full factorial treatment combination of four salinity levels and four disturbance regimes during three consecutive years. Both in the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
1
24
2
Order By: Relevance
“…Copepod nauplii were the least tolerant to salt in our experiment. It is possible that a sublethal effect of salinity suppressed reproductive output but survival was unaffected (Waterkeyn et al 2011). We did not observe a direct impact of salt on overall cladoceran abundance in the absence of fish.…”
Section: Zooplanktoncontrasting
confidence: 59%
See 1 more Smart Citation
“…Copepod nauplii were the least tolerant to salt in our experiment. It is possible that a sublethal effect of salinity suppressed reproductive output but survival was unaffected (Waterkeyn et al 2011). We did not observe a direct impact of salt on overall cladoceran abundance in the absence of fish.…”
Section: Zooplanktoncontrasting
confidence: 59%
“…At the community level, Van Meter et al (2011a) concluded high chloride levels (645 mg/L) reduced competitive interactions for algal resources between tadpole and zooplankton grazers. In some cases, salinization can alter community succession and wipe out many sensitive zooplankton species (Waterkeyn et al 2010(Waterkeyn et al , 2011. Salinization can also act as an environmental filter by altering community structure toward salt-tolerant species in wetland (Petranka and Doyle 2010, Van Meter et al 2011b, Van Meter and Swan 2014, and lotic ecosystems (Cañedo-Argüelles et al 2016b, Kefford et al 2016, Wallace and Biastoch 2016.…”
Section: Introductionmentioning
confidence: 99%
“…, 2010), although at higher salinities there may be reduced viability of some eggs from freshwater species (Bailey et al. , 2003; Waterkeyn et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that in brackish and other transitional waters species richness is lower than in freshwater and marine habitats (Remane, 1934). Previously published data show that freshwater zooplankton species, mostly rotifers and cladocerans, show low tolerance to increasing salinity (Hart et al, 1991; Boronat et al, 2001;Nielsen et al, 2003Nielsen et al, , 2012North and Houde, 2003;Waterkeyn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant change occurred in assemblages of Cladocera, Rotifera and Bacillariophyta that were very abundant in 2008, but almost completely disappeared in 2009 (See List of taxa and their abundances in two investigation years after References). A lot of field and experimental studies have proved that the abundance and species richness of assemblages of Rotifera and Cladocera decreases with the increase of habitat salinization (Boronat et al, 2001;Nielsen et al, 2003;Waterkeyn et al, 2011). Hart et al (1991) showed that freshwater Cladocera are less tolerant to salinities above 1000 mg.L x1 (2000 mS.cm x1 ).…”
Section: Discussionmentioning
confidence: 99%